Paracoccidioides brasiliensis: phylogenetic and ecological aspects - Bagagli, Eduardo [UNESP]; Theodoro, Raquel C. [UNESP]; Bosco, Sandra M. G. [UNESP]; McEwen, Juan G. (Springer, 2008)
The knowledge on the biological aspects of Paracoccidioides brasiliensis has evolved greatly since the first description of the disease in 1908. From the pioneers, who were able to clearly demonstrate the fungal nature of the agent, to the recent genomic era, important advances have been achieved. P. brasiliensis is a true fungus, belonging to the Ascomycetous Division, although its sexual phase has not been demonstrated morphologically. A better understanding of the fundamental aspects of the agent, especially its phylogeny and evolutionary history, will provide us with valuable insights allowing a better comprehension of the disease and our capacity to deal with the problem. Concerning the fungus's ecology, although some progress had been observed, the ecological niche of the pathogen has not been determined yet. The aim of the present review is to focus on the biological aspects of P. brasiliensis from an evolutionary point of view, addressing the fungus's phylogenetic aspects, in those special points that might be relevant for the pathogen/host interactions, the biological forces that have been acting on its origin and maintenance of virulence, as well as in determining the fungus's ecology and epidemiology.
Keywords: Paracoccidioides brasiliensis; paracoccidioidomycosis; ecology; evolution; phylogeny